PENYULUHAN PENCEGAHAN STUNTING DENGAN MEMANFAATKAN PANGAN KUKIS BERBAHAN TEPUNG KOMPOSIT DAN TEPUNG IKAN - Lopulalan, Cynthia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2023)
This PkM activity aims to provide education about non-wheat food processing that is available in the community and increase knowledge about the dangers of stunting. The method used is direct outreach through the introduction of cookies made from composites and skipjack tuna flour. The results obtained showed extraordinary enthusiasm from the counseling participants. Understanding of the use of local raw materials to produce products with nutritional value is increasing. Children's interest in non-wheat KUKIS is very good. The other interested from children because cookies are made in various cute shapes.